Metabolic optimisation of the basketball free throw - Padulo, J.; Attene, G.; Migliaccio, G. M.; Cuzzolin, F.; Vando, S.; Ardigò, L. P. (Journal of Sports Sciences, 2015)
The free throw (FT) is a fundamental basketball skill used frequently during a match. Most of actual play occurs at about 85% of maximum heart rate (HR). Metabolic intensity, through fatigue, may influence a technically skilled move as the FT is. Twenty-eight under 17 basketball players were studied while shooting FTs on a regular indoor basketball court. We investigated FT accuracy in young male basketball players shooting at three different HRs: at rest, at 50% and at 80% of maximum experimentally obtained HR value. We found no significant FT percentage difference between rest and 50% of the maximum HR (FT percentage about 80%; P > 0.05). Differently, at 80% of the maximum HR the FT percentage decreased significantly by more than 20% (P < 0.001) down to about 60%. No preliminary warm-up is needed before entering game for the FT accuracy. Furthermore, we speculate that time-consuming, cooling-off routines usually performed by shooters before each FT may be functional to improve its accuracy.